Building subjective well-being indicators at the subnational level A preliminary assessment in OECD regions - Brezzi, Monica (OECD Regional Development Working Papers, 2016)
This paper provides, for the first time, estimates of subjective well-being variables in 373 OECD subnational regions, allowing comparison of various measures of how people experience and evaluate their lives within and across all 34 OECD countries. Different weighting strategies as well as several robustness checks have been carried out to ensure regional representativeness and to provide reliable indicators. The results show that it is possible to obtain robust regional estimates of subjective well-being through the Gallup World Poll for the variables satisfaction with life and social support network. These estimates could be included in the OECD Regional Well-Being Database to provide two additional well-being dimensions measured uniquely with subjective indicators.